Development of Strategies to Reduce Ventilation and Heating Costs in a Swedish Sublevel Caving Mine—a Unique Case of LKAB’s Konsuln Mine - Gyamfi, S.; Halim, Adrianus; Martikainen, A. (Mining, Metallurgy & Exploration, 2022)
This paper outlines a unique case of the development of strategies to reduce ventilation and heating costs in Konsuln iron ore mine in northern Sweden. The mine, located just south of Luossavaara-Kiirunavaara Aktiebolag’s Kiruna iron ore mine, was developed as a test mine 2018–2020 for the Sustainable Underground Mining (SUM) project. Besides functioning as a test mine, Konsuln also contributes ore production. The existing mine ventilation system was designed for the current production rate of 0.8 million tons per annum (Mtpa). There is a plan to increase this rate to between 1.8 and 3 Mtpa in the future, and this requires the primary fans to be upgraded. Therefore, a study was carried out to determine whether using ventilation on demand (VOD) could avoid this fan upgrade and reduce Konsuln’s ventilation and heating power costs in the future. The study also investigated whether using battery electric vehicles (BEVs) along with VOD or as a standalone strategy could further reduce these power costs. In addition, the study analyzed the suitability of heating power reduction strategies presently or previously used in the Nordic countries and Canada to investigate potential additional strategies to reduce the heating power cost, the largest portion of Konsuln’s ventilation and heating power costs. The study found using VOD can avoid the expensive upgrading of the existing primary fans and reduce Konsuln’s ventilation and heating power costs in the future. Using BEVs can further reduce these costs. Finally, none of the Nordic and Canadian heating power reduction strategies is suitable for Konsuln because they require unique conditions that do not exist in Konsuln. Validerad;2022;Nivå 2;2022-03-15 (hanlid); For correction, see: Gyamfi, S., Halim, A. & Martikainen, A. Correction to: Development of Strategies to Reduce Ventilation and Heating Costs in a Swedish Sublevel Caving Mine—a Unique Case of LKAB’s Konsuln Mine. Mining, Metallurgy & Exploration 39, 239 (2022). https://doi.org/10.1007/s42461-021-00538-0